Demand and Supply Functions for Stocks of Eurodollar Deposits: Reply - Makin, John H. (The Review of Economics and Statistics, 1975)
over this business would depend upon the size of the advantage and the rate with which the advantage becomes recognized. The apparent parabolic growth path displayed by Eurodollar deposits so far is consistent with theories of the early stages of a new product. The path of Eurodollar expansion can be formulated as a cumulative response to a gradually recognized cost advantage. Such factors as the stringencies of Regulation Q ceilings on interest rates and the exchange controls can be viewed as sources of the residual variation from the growth path.